2022
DOI: 10.1088/1361-6528/ac5aee
|View full text |Cite
|
Sign up to set email alerts
|

Silver-decorated black phosphorus: a synergistic antibacterial strategy

Abstract: Black phosphorus (BP) exhibits great potential as antibacterial materials due to its unique photocatalytic activity. However, the unsatisfactory optical absorption and quick recombination of photoinduced electron–hole pairs restrain its photocatalytic antibacterial performance. In this work, silver nanoparticles (AgNPs) were decorated on BP to construct BP@AgNPs nanohybrids and then introduced into polymer scaffold. On one hand, AgNPs with broad optical absorption range could improve the light absorption abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…In the case of the PLLA/GO scaffold, two peaks at 1743 and 3453 cm –1 were detected in the spectra, which were assigned to the stretching vibration of CO belonging to PLLA and the hydroxyl group, respectively . In the case of the PLLA/ZIF@GO scaffold, the hydroxyl group and CO peak were redshifted, indicating hydrogen bonding between ZIF@GO and PLLA …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In the case of the PLLA/GO scaffold, two peaks at 1743 and 3453 cm –1 were detected in the spectra, which were assigned to the stretching vibration of CO belonging to PLLA and the hydroxyl group, respectively . In the case of the PLLA/ZIF@GO scaffold, the hydroxyl group and CO peak were redshifted, indicating hydrogen bonding between ZIF@GO and PLLA …”
Section: Resultsmentioning
confidence: 98%
“…43 In the case of the PLLA/ ZIF@GO scaffold, the hydroxyl group and CO peak were redshifted, indicating hydrogen bonding between ZIF@GO and PLLA. 44 In general, the oxygenated functional group of the GO nanosheets possessed high surface activity, which made it difficult to form good interface bonds with PLLA with low polarity. Overall, these results indicated that the ZIF-8@GO nanosystem effectively alleviated the agglomeration of GO in the PLLA matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The cytocompatibility of scaffolds is a necessary and crucial element in the bone repair process because it determines whether cells can adhere, grow, and proliferate on the scaffold [ 36 , 37 ]. Herein, the cytocompatibility of the PLLA, PLLA/Fe 3 O 4 and PLLA/Fe 3 O 4 @SiO 2 scaffolds were assessed.…”
Section: Resultsmentioning
confidence: 99%
“…The cells cultured on all extracts showed obvious proliferation with the increase of culture time, which was consistent with the CCK-8 results. Moreover, the cells remained healthy and showed a clear trend of expansion, indicating that the degradation products had little effect on cell growth and metabolic activities. To sum up, both CCK-8 assay and fluorescence staining results demonstrated good biocompatibility of the Fe30Mn6Si alloy. The higher cell viability attributed to the release of Si 4+ in the degradation process was beneficial to osteoblasts’ proliferation and differentiation .…”
Section: Resultsmentioning
confidence: 99%